Implementasi Penyembunyian Dokumen DOCX Menggunakan Enkripsi AES (Fernet) dan Teknik File Fusing Berbasis Python - Achmadurramzi Achmadurramzi; Ashraf Zaky; Danil Muzakki; Ikhlasul Amal (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
This study discusses the implementation of a document concealment technique for DOCX files using a combination of AES (Fernet) encryption and a Python-based file fusing method. The main objective of this research is to enhance file-level data security by encrypting document content and embedding it within a host file (e.g., an image) without altering the functionality of the host file. The research methodology includes the analysis of the AES algorithm, encryption and decryption processes, the implementation of file fusing, and performance evaluation in terms of time efficiency and file size growth. The results show that this method effectively maintains document confidentiality while making the hidden data difficult to detect, with the combined file size increasing only by approximately 2–5% from the original host file. This system can be applied for securing confidential data in digital environments, particularly for online distribution of sensitive documents.